Analisis Determinan Keandalan Pelaporan Keuangan Pemerintahan Desa Di Kabupaten Deli Serdang - Annisa Rizkia; Ratna Sari Dewi; Ova Novi Irama; Debby Chyntia Ovami (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to determine and analyze the influence of the Quality of Human Resources, Utilization of Information Technology, Internal Control Systems on the Reliability of Village Financial Reporting in Deli Serdang Regency. This research uses quantitative methods. The data collection method uses a questionnaire distributed directly to respondents. The respondents in this study were 52 respondents, namely the village treasurer and village secretary in Tanjung Morawa District, Deli Serdang Regency. As a data acquisition tool used is primary data and the measuring tool uses a Likert scale. This research was conducted in the village of Tanjung Morawa subdistrict. The sampling technique used is saturated sampling in which all members of the population are sampled. The data analysis used is multiple linear regression analysis using the SPPS program version 20. Based on the results of the analysis and discussion of the research results, it shows that the variables Human Resources (X1), Utilization of Information Technology (X2), Internal Control System (X3) are Partial and Simultaneous have a positive and significant influence on the Reliability of Financial Reporting (Y).